Transformational Leadership in Education: Enhancing Teacher Performance through Effective Management - Muhammad Zailani Iman; Ayu Monic Veronica (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
Transformational leadership has been identified as an effective approach to mitigate these challenges by fostering supportive, innovative, and empowering school environments. This study aims to investigate the multifaceted influence of transformational leadership on teacher performance enhancement, burnout reduction, and professional development through effective management practices. Employing a library research methodology, the study synthesizes recent empirical evidence and theoretical frameworks from peer-reviewed literature published within the past five years. Data were collected and analyzed through systematic review and thematic synthesis of scholarly articles focusing on transformational leadership in educational settings. The findings demonstrate that transformational leadership substantially enhances teacher motivation and job satisfaction by providing individualized support and cultivating a shared sense of purpose. Instructional support through mentoring, guidance, and feedback strengthens teaching effectiveness, while a positive school climate mediated by transformational leadership fosters trust and collaboration. Furthermore, transformational leadership promotes continuous professional learning and pedagogical innovation by creating psychologically safe environments conducive to reflection and experimentation.